Neisseria gonorrhoeae lipooligosaccharide glycan epitopes recognized by bactericidal IgG antibodies elicited by the meningococcal group B-directed vaccine, MenB-4C - Tzeng, Yih-Ling; Sannigrahi, Soma; Borrow, Ray; Stephens, David S. (Frontiers in Immunology, 2024)
Introduction Outer membrane vesicles (OMVs) of Neisseria meningitidis in the group B-directed vaccine MenB-4C (BexseroR) protect against infections with Neisseria gonorrhoeae. The immunological basis for protection remains unclear. N. meningitidis OMV vaccines generate human antibodies to N. meningitidis and N. gonorrhoeae lipooligosaccharide (LOS/endotoxin), but the structural specificity of these LOS antibodies is not defined. Methods Ten paired human sera obtained pre- and post-MenB-4C immunization were used in Western blots to probe N. meningitidis and N. gonorrhoeae LOS. Post-MenB-4C sera (7v5, 19v5, and 17v5), representing individual human variability in LOS recognition, were then used to interrogate structurally defined LOSs of N. meningitidis and N. gonorrhoeae strains and mutants and studied in bactericidal assays. Results and discussion Post-MenB-4C sera recognized both N. meningitidis and N. gonorrhoeae LOS species, ~10% of total IgG to gonococcal OMV antigens. N. meningitidis and N. gonorrhoeae LOSs were broadly recognized by post-IgG antibodies, but with individual variability for LOS structures. Deep truncation of LOS, specifically a rfaK mutant without α-, β-, or γ-chain glycosylation, eliminated LOS recognition by all post-vaccine sera. Serum 7v5 IgG antibodies recognized the unsialyated L1 α-chain, and a 3-PEA-HepII or 6-PEA-HepII was part of the conformational epitope. Replacing the 3-PEA on HepII with a 3-Glc blocked 7v5 IgG antibody recognition of N. meningitidis and N. gonorrhoeae LOSs. Serum 19v5 recognized lactoneotetrose (LNT) or L1 LOS-expressing N. meningitidis or N. gonorrhoeae with a minimal α-chain structure of Gal-Glc-HepI (L8), a 3-PEA-HepII or 6-PEA-HepII was again part of the conformational epitope and a 3-Glc-HepII blocked 19v5 antibody binding. Serum 17v5 LOS antibodies recognized LNT or L1 α-chains with a minimal HepI structure of three sugars and no requirement for HepII modifications. These LOS antibodies contributed to the serum bactericidal activity against N. gonorrhoeae. The MenB-4C vaccination elicits bactericidal IgG antibodies to N. gonorrhoeae conformational epitopes involving HepI and HepII glycosylated LOS structures shared between N. meningitidis and N. gonorrhoeae. LOS structures should be considered in next-generation gonococcal vaccine design.